Ceramic tile with surface having bright and matte combination effect and preparation method of ceramic tile
By using a combination of specific dry granular glaze and inkjet functional ink layer in ceramic tiles, the problems of complex preparation and poor stain resistance of existing three-dimensional effect ceramic tiles are solved, achieving a bright sub-combination effect and a multi-dimensional three-dimensional gloss effect, and improving the product's Fine feel and durability.
Patent Information
- Application Number
- CN202411486074.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-10-23
AI Technical Summary
The existing ceramic tiles with three-dimensional effects rely on concave and convex structures to form, the preparation method is complex and the brick surface has poor stain resistance, which affects the decorative effect.
The structure of the blank layer, bottom glaze layer, inkjet function ink and surface glazed layer is adopted in order. The surface glazed layer includes dry grain glaze. Dry grains contain specific proportions of Al2O3, SRO, BAO and other ingredients, combined with high temperature firing of sub -light ink and bright ink, to achieve the combination of bright Asia and multi -dimensional three -dimensional luster effects.
A combination of tiles and the multi -dimensional three -dimensional luster effect of the tiles improve the delicate and advanced sense of the product, and at the same time improve the surface flatness, anti -dirt resistance, wear resistance and friction coefficient.
Smart Images

Figure CN119330753A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of ceramic tiles, and in particular relates to a ceramic tile with a bright matte bonding effect on the surface and a preparation method thereof. Background Art
[0002] With the improvement of living standards, people's taste for interior decoration effects is also getting higher, and the requirements for tiles are getting higher and higher. At present, there are many types of tiles in the building ceramics industry: polished tiles, antique tiles, fully glazed tiles, dry granular glazed tiles, microcrystalline stones, etc. The above categories of tiles have their own characteristics and meet the different needs of consumers to a certain extent. Among them, tiles with three-dimensional effects are very popular because of their special visual effects. Existing tiles with three-dimensional effects generally form an uneven structure on the brick surface through physical carving to achieve a three-dimensional effect, or through the organic solvent in the fine carving ink to repel the water-based surface glaze slurry, forming an uneven structure on the brick surface to achieve a three-dimensional effect. However, although this uneven structure can produce a three-dimensional effect, it is also easy to hide dirt and dirt because of its uneven surface. It is not only difficult to take care of, but also easy to affect the decorative effect over time. Summary of the invention
[0003] The purpose of the present invention is to solve the defects of existing ceramic tiles with three-dimensional effects, which rely on concave-convex structures, have complex preparation methods, and poor stain resistance of the tile surface, and further provide a ceramic tile with a bright and matte combination effect on the surface, the ceramic tile comprises a body layer, a bottom glaze layer, an inkjet functional ink layer, and a surface glaze layer stacked in sequence; the surface glaze layer comprises dry particle glaze, the dry particle glaze comprises dry particles, and the dry particles comprise, by mass percentage: Al2O3 17%-20%, SrO 4.5%-6.5%, BaO14%-17%; the particle size of the dry particles is 250-400 mesh; the inkjet functional ink layer comprises matte ink and glossy ink, the gray amount of the matte ink is 30%-60%, and the gray amount of the glossy ink is 50%-100%.
[0004] The dry particles specially proposed in the present invention can interact with the functional inks including matte ink and glossy ink through high-temperature firing, thereby ensuring that the glaze of the tile has good flatness and strong color development ability, while better promoting the stability of the gloss of the glossy ink and matte ink, so that the tile has a better gloss-matt combination effect, and achieves a multi-dimensional three-dimensional gloss effect with multiple levels of gloss (matte 3-10 degrees, glaze 15-25 degrees, gloss 50-80 degrees), thereby enhancing the delicacy and high-end feel of the product.
[0005] The present invention achieves the above-mentioned effects well by exploring and proposing the above-mentioned dry particles among numerous ceramic raw materials; among them, the most critical thing is to limit the content of BaO to 14%-17% (different from the commonly used amount of the raw material of 0.05%-2%), and barium oxide is mainly introduced in the form of barium carbonate, which has a significant melting effect, can help reduce the melting temperature and high-temperature viscosity of the glaze at high temperature, thereby improving the fluidity and glossiness of the glaze surface, and in the system of the present invention, limiting its amount to an appropriate amount, that is, 14%-17%, can significantly improve the refractive index and glossiness of the glaze surface, and realize the multi-dimensional gloss presentation of glossy ink and matte ink; if the content of BaO in the dry particle composition is lower than 14%, it will affect the gloss of the glaze surface to the glossy ink, and will also affect the gloss of the matte ink to a certain extent. If the content exceeds 17%, barium silicate crystals are more likely to precipitate during the high temperature process, which will also affect the glaze surface to lose gloss of the glossy ink. Both will eventually cause the tile to lose the glossy and matte combination effect and the multi-dimensional three-dimensional gloss effect. In addition, the bright sub-combination effect and multi-dimensional three-dimensional gloss effect of the ceramic tile are also affected by factors such as the flatness of the glaze. The present invention controls the content of Al2O3 between 17% and 20% because Al2O3 can regulate the firing temperature. The higher the content, the higher the firing temperature, and the glaze flatness will decrease. The lower the content, the lower the firing temperature, and the frosting degree / hand feel of the glaze decreases. Both will make the ceramic tile unable to achieve the bright sub-combination effect and multi-dimensional three-dimensional gloss effect. Only within this range can a good glaze flatness and frosting degree / hand feel be guaranteed, thereby ensuring the realization of the bright sub-combination effect and multi-dimensional three-dimensional gloss effect. The present invention controls the content of SrO to 4.5%-6.5% because SrO can better ensure the color stability of the glaze and reduce the cracking rate only within this range. The present invention controls the particle size of dry particles to be 250-400 meshes, because if the mesh number is too large, it will seriously affect the surface flatness of the tile, and if the mesh number is too small, the hand feel will be rough, the dirt absorption will be serious, the color will be weak, and the above-mentioned bright and matte combination effect and multi-dimensional three-dimensional gloss effect cannot be achieved. In addition, the present invention also needs to limit the gray amount of matte ink to 30%-60%, and the gray amount of glossy ink to 50%-100%; if the gray amount of matte ink is too high, that is, its content is too much, it will cause the final product to easily absorb dirt and affect the clarity of the possible printed pattern. If the gray amount of glossy ink is less than 50%, the gloss effect of the final product will be poor.
[0006] It should be noted that the biggest technical difficulty in the research process of the present invention is to explore specific materials among the numerous raw materials of ceramics and to match them within a specific content range when there are still unknown interactions between them. In addition, the above-mentioned dry particle composition not only interacts with itself, but also needs to be designed to interact with glossy ink and matte ink to stabilize the gloss of the ink, thereby achieving a glossy and matte combination effect and a multi-dimensional three-dimensional gloss effect.
[0007] In addition, the dry particles used in the present invention can also make the tiles have the characteristics of no dirt hiding, wear resistance, excellent friction coefficient, etc. The frosted feeling allows the light to form a uniform diffuse reflection on the glaze surface, better creating a comfortable and warm living environment, and well solving the problem of existing "three-dimensional effect" tiles with serious dirt hiding and dazzling light reflection.
[0008] In some preferred embodiments, the dry particles include, by mass percentage, SiO2 40%-45%, Al2O3 17%-20%, CaO 1.5%-3.5%, Na2O 4.5%-6.5%, K2O 1.5%-3.5%, ZrO2 0.1%-0.5%, Fe2O3
[0009] 0.05%-0.15%, ZnO 5.5%-7.5%, P2O5 0.1%-0.2%, BaO 14%-17%, SrO4.5%-6.5%, MgO 0.5%-2.0%, TiO2 0.01%-0.1%, CuO 0.01%-0.1%, HfO2 0.01%-0.03%, PbO 0.01%-0.08%, Mn3O40.01%-0.05%, SO3 0.01%-0.05%, ignition reduction 0.1%-1.5%.
[0010] In some preferred implementations, the dry particle glaze comprises, by mass percentage, 15%-25% of the dry particles, 70%-80% of the suspending agent, and 5%-15% of the protective glaze slurry. The above protective glaze slurry may include, by mass percentage: SiO2 45%-50%, Al2O3 14%-17%, CaO 4.0%-6.0%, Na2O 1.0%-3.0%, K2O 3.5%-5.5%, Fe2O3 0.15%-0.25%, ZnO 3.5%-5.5%, P2O5 0.1%-0.3%, BaO 4.5%-6.5%, SrO 1.5%-3.0%, MgO 3.0%-5.0% (with good fluxing effect), TiO2 0.05%-0.15%, HfO2 0.0%-0.05%, SO3 0.01%-0.05%, V2O5
[0011] 0.02-0.08%, burning reduction 5.5%-8.5%.
[0012] The present invention finds that the introduction of protective glaze slurry into the dry granular glaze can further ensure the fineness and smoothness of the glaze surface without affecting the color development ability, better achieve the bright and sub-bright combination effect and the multi-dimensional three-dimensional gloss effect, and can further improve the anti-fouling effect of the ceramic tile, and can ensure that the firing temperature is controlled within a wider range so that the temperature can be adjusted to achieve stable mass production.
[0013] The suspending agent may be HB-818A, which may include, by mass, 28-38 parts of deionized water, 15-25 parts of methyl glycol, 15-25 parts of sodium carboxymethyl cellulose, 15-25 parts of polymethylsiloxane, 3-6 parts of sodium dodecylbenzene sulfonate (dispersant), and 2-4 parts of sodium hydroxide pH regulator. Sodium dodecylbenzene sulfonate (dispersant) helps to improve overall suspension and fluidity, polymethylsiloxane and sodium carboxymethyl cellulose are used together to enhance the viscosity and suspension dispersion performance of the suspending agent, deionized water is used as a common solvent, methyl glycol has the function of adjusting the suspension consistency, and sodium hydroxide pH regulator is an acid-base regulator.
[0014] In some preferred implementations, the above-mentioned matte ink includes, by mass, 4-6 parts of high-temperature frit, 9-11 parts of fused quartz, 2-3 parts of calcined zinc oxide, 13-16 parts of zirconium silicate, 3-7 parts of diaspore, 2-4 parts of bismuth oxide, 4-6 parts of polyurethane dispersant, and 45-60 parts of methyl oleate; the above-mentioned high-temperature frit includes, by mass percentage, 45%-55% of SiO2, 28%-35% of Al2O3, 3.5%-6.5% of K2O, 3.5%-6.5% of Na2O, 3.5%-6.5% of ZnO, and 4%-6% of CaO.
[0015] The above-mentioned bright ink includes, by mass, 4-6 parts of medium-temperature frit, 9-11 parts of fused quartz, 2-3 parts of calcined zinc oxide, 13-16 parts of zirconium silicate, 3-7 parts of diaspore, 2-4 parts of bismuth oxide, 4-6 parts of polyurethane dispersant, and 45-60 parts of methyl oleate; the above-mentioned medium-temperature frit includes, by mass percentage, 49%-59% of SiO2, 16%-22% of Al2O3, 3.5%-7.5% of K2O, 3.5%-7% of Na2O, 4.5%-7.5% of ZnO, and 4%-7% of CaO.
[0016] In some preferred implementations, an inkjet printing layer is further provided between the base glaze layer and the inkjet functional ink layer.
[0017] The base glaze forming the base glaze layer may include, by mass percentage, 15%-25% potassium feldspar, 20%-30% sodium feldspar, 6%-14% air knife clay, 7%-14% nepheline feldspar, 5%-10% quartz, 3%-9% wollastonite, 2%-8% zinc oxide, 5%-10% aluminum oxide, and 10%-15% zirconium silicate. More preferably, the base glaze may include, by mass percentage, 20% potassium feldspar, 25% sodium feldspar, 10% air knife clay, 10% nepheline feldspar, 7% quartz, 5% wollastonite, 3% zinc oxide, 8% aluminum oxide, and 12% zirconium silicate.
[0018] The green material for the green body layer may include, by mass percentage, 67.5% silicon dioxide, 18.8% aluminum oxide, 2.5% potassium oxide, 2.5% sodium oxide, 0.5% calcium oxide, 1.5% magnesium oxide, and other minor impurities. The fineness of the powder is controlled to be 1.0% on a 250 mesh sieve, and then spray granulated, and the gradation is controlled to be less than 5% at 30 mesh, 30% at 40 mesh, 62% at 60 mesh, and no more than 5% at 100 mesh.
[0019] By using the above-mentioned base glaze, dry granule glaze and body material, the body, base glaze and surface glaze constituting the tile can be better bonded. In addition, the base glaze, functional ink layer, and dry granule glaze configured with dry granules can work together to achieve a multi-dimensional three-dimensional bright and sub-bright bonding effect. In particular, the configuration of the dry granules of the present invention is a result of multiple formula tests, and the most matching temperature optimization and content range of each raw material are adopted to ensure that the interaction with the glossy ink and the sub-gloss ink during the high-temperature firing process is more compatible, thereby better achieving a multi-dimensional three-dimensional bright and sub-bright bonding effect.
[0020] The present invention also provides a method for preparing the ceramic tile having the above-mentioned surface having a bright sub-bonding effect, comprising the following steps:
[0021] Prepare the above green body layer (specifically, it can be powder making, spreading and drying);
[0022] Applying ground glaze on the surface of the green body layer to form the ground glaze layer;
[0023] Then, the matte ink and the glossy ink are inkjetted to form the inkjet functional ink layer;
[0024] Applying the dry granular glaze on the surface of the inkjet functional ink layer to form the surface glaze layer;
[0025] Fire it to get the above-mentioned tiles.
[0026] When an inkjet printing layer is also provided, the method further comprises the step of jetting ink onto the base glaze layer to form the inkjet printing layer.
[0027] In some preferred implementations, the fired product is subjected to a brush polishing treatment to obtain the ceramic tile; the brush polishing treatment includes the following processes: brush polishing with a 2000 mesh resin film for 25s-35s, fine polishing with a 240 mesh fiber module for 45s-55s, and fine polishing with a 240 mesh plastic silicon carbide grinding brush for 25s-35s. The pressure during brush polishing with the resin grinding disc is 1.0MPa-1.5MPa; the pressure during fine polishing with the fiber module and the plastic silicon carbide grinding brush is 1.0MPa-1.5MPa. After the brush polishing treatment, the surface flatness of the ceramic tile is further improved.
[0028] In some preferred implementations, when forming the inkjet functional ink layer, the matte ink and the glossy ink are sprayed so that the grayscale of the matte ink and the glossy ink presents a gradient change. That is, the matte ink and the glossy ink are sprayed on the surface to be sprayed according to the gradient grayscale, which can bring about a more natural transition color presentation.
[0029] In some preferred implementations, the specific gravity of the base glaze is 1.80 g / mL-1.86 g / mL, and the glaze application amount is 450 g / m 2 -550g / m 2 , the flow rate is 35s-45s; applying the base glaze under this condition can better ensure that the surface of the tile is smoother and the structure is more stable. The specific gravity of the above dry granular glaze is 1.35g / mL-1.5g / mL, and the glaze amount is 300g / m 2 -400g / m 2 The dry granules can be prepared according to the following steps: mixing raw materials that meet the conditions, melting them at high temperature and then pouring them into water for quenching to obtain dry granule frits, and then awakening, crushing and classifying them to obtain the dry granules.
[0030] The firing conditions include: a firing temperature of 1180°C-1210°C and a firing time of 45min-65min. The firing temperature can improve the surface effect of the fired ceramic tile.
[0031] The beneficial effects of the present invention are as follows: after the specific dry particle glaze proposed by the present invention interacts with the bright sub-functional ink through high-temperature firing, the obtained tiles have good bright sub-effect and multi-dimensional three-dimensional gloss effect, and also have good surface flatness, color development ability, friction coefficient, anti-slip, wear resistance, anti-fouling and other characteristics; its preparation method is simple and easy, the production is stable, and it has great promotion value. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 Shown is a photograph of a tile made using the method of Example 1 except for the inkjet functional ink step;
[0033] Figure 2 Shown is a photograph of the tile produced in Example 1. DETAILED DESCRIPTION
[0034] The following will be combined with the embodiments and drawings to clearly and completely describe the concept and technical effects of the present invention, so as to fully understand the purpose, scheme and effect of the present invention. It should be noted that the embodiments and features in the embodiments of the present invention can be combined with each other without conflict.
[0035] Example 1
[0036] A ceramic tile with a bright sub-combination effect on the surface, comprising a body layer, a base glaze layer, an inkjet printing layer, an inkjet functional ink layer, and a surface glaze layer which are sequentially stacked; the surface glaze layer comprises a dry particle glaze, the dry particle glaze comprises dry particles, and the dry particles comprise, by mass percentage, SiO2 42.89%, Al2O3 18.5%, CaO 2.04%, Na2O 5.20%, K2O 1.86%, ZrO2 0.12%, Fe2O3 0.09%, ZnO 6.11%, P2O5 0.14%, BaO 15.74%, SrO 5.76%, MgO 0.9%, TiO2 0.04%, CuO 0.01%, PbO 0.04%, HfO2 0.03%, SO3 0.02%, Mn3O4 0.01%, ignition reduction 0.5%; the particle size of the dry particles is 250-320 mesh. The inkjet functional ink layer includes matte ink 131-8 (gray content 30%-60%) and glossy ink CZN00045 (gray content 50%-100%).
[0037] The method for preparing the ceramic tile comprises the following steps:
[0038] (1) Prepare a ceramic body layer; after powdering, spreading and drying, a ceramic body layer is obtained, and the water absorption rate is ≤0.5%; wherein the ceramic body powder is composed of the following components by mass percentage: 67.5% silicon dioxide, 18.8% aluminum oxide, 2.5% potassium oxide, 2.5% sodium oxide, 0.5% calcium oxide, 1.5% magnesium oxide, and the rest is reduced and trace impurities. The powder fineness is controlled to 1.0% on a 250 mesh sieve, and then spray granulated, and the gradation is controlled to be: less than 5% at 30 mesh, 30% at 40 mesh, 62% at 60 mesh, and no more than 5% at 100 mesh;
[0039] (2) Applying a base glaze on the surface of the ceramic body layer to form a base glaze layer; wherein the base glaze has a specific gravity of 1.84 g / mL, a flow rate of 40 s, and a glaze amount of 450 g / m 2 ;
[0040] The base glaze is composed of the following components by mass percentage: potassium feldspar 20%, sodium feldspar 25%, air knife clay 10%, nepheline feldspar 10%, quartz 7%, wollastonite 5%, zinc oxide 3%, aluminum oxide 8%, zirconium silicate 12%;
[0041] (3) printing an inkjet printing layer on the surface of the base glaze layer;
[0042] (4) printing a functional ink layer on the inkjet printing layer (wherein: the grayscale of matte ink 131-8 is 30%-60%, and the grayscale of glossy ink CZN00045 is 50%-100%); the matte ink and the glossy ink are jetted according to a gradient grayscale, so that the matte ink and the glossy ink on the surface of the inkjet printing layer are distributed in a gradient grayscale;
[0043] Matt ink includes by mass: 5 parts of high-temperature frit, 10 parts of fused quartz, 3 parts of calcined zinc oxide, 14 parts of zirconium silicate, 5 parts of diaspore, 3 parts of pyrolysis, 5 parts of Foshan Koning polyurethane dispersant UV-531, 5 parts of methyl oleate; the high-temperature frit includes by mass percentage: SiO2 51%, Al2O3 30%, K2O 5%, Na2O 4%, ZnO4%, CaO 6%;
[0044] The glossy ink includes, by mass, 5 parts of medium-temperature frit, 10 parts of fused quartz, 2 parts of calcined zinc oxide, 15 parts of zirconium silicate, 6 parts of diaspore, 2 parts of pyrolysis, 6 parts of Foshan Koning polyurethane dispersant UV-531, and 54 parts of methyl oleate; the medium-temperature frit includes, by mass percentage, 55% SiO2, 20% Al2O3, 6.5% K2O, 6.5% Na2O, 6% ZnO, and 6% CaO;
[0045] (5) applying dry particle glaze on the surface of the functional ink layer to form a surface glaze layer; wherein the dry particle glaze is composed of the following components by mass percentage: 20% dry particles, 75% suspending agent, and 5% protective glaze slurry;
[0046] The protective glaze slurry is composed of the following chemical components by mass percentage: SiO2 49%, Al2O3 16.57%, CaO5.26%, Na2O 1.68%, K2O 4.03%, Fe2O3 0.19%, ZnO 4.25%, P2O5 0.23%, BaO 5.02%, SrO
[0047] 2.36%, MgO 3.89%, TiO2 0.09%, HfO2 0.05%, SO3 0.04%, V2O5 0.04%, ignition loss 7.30%;
[0048] The suspending agent is HB-818A, which includes the following components by mass: 32 parts of deionized water, 20 parts of methyl glycol, 20 parts of sodium carboxymethyl cellulose, 20 parts of polymethylsiloxane, 5 parts of sodium dodecylbenzene sulfonate (dispersant), and 3 parts of sodium hydroxide (pH regulator).
[0049] The specific gravity of dry granular glaze is 1.4g / mL, the flow rate is 35s, the 325 mesh residue is 1.2%, and the glaze amount is 300g / m 2 ;
[0050] (6) firing to obtain a primary finished tile product; wherein the firing temperature is 1200° C. and the firing time is 50 min;
[0051] (7) Use a 2000-mesh resin abrasive disc for micro-brush polishing for 30 seconds, wherein the pressure of the resin abrasive disc on the ceramic tile pre-finished product is 1.0 MPa, then use 8 groups of 240-mesh fiber modules for fine polishing for 50 seconds and 5 groups of 240-mesh plastic silicon carbide grinding brushes for fine polishing for 30 seconds, wherein the pressure of the fiber module and the plastic silicon carbide grinding brush on the ceramic tile pre-finished product is 1.5 MPa, and after applying anti-fouling wax water, the ceramic tile finished product is obtained.
[0052] Example 2
[0053] A ceramic tile with a bright sub-combination effect on the surface, comprising a body layer, a base glaze layer, an inkjet printing layer, an inkjet functional ink layer, and a surface glaze layer which are sequentially stacked; the surface glaze layer comprises a dry granular glaze, the dry granular glaze comprises dry particles, and the dry particles comprise, by mass percentage, SiO2 41.79%, Al2O3 20%, CaO 1.54%, Na2O 4.7%, K2O 1.96%, ZrO2 0.12%, Fe2O3
[0054] 0.09%, ZnO 6.11%, P2O5 0.14%, BaO 16.24%, SrO 5.76%, MgO 0.9%, TiO2 0.04%, CuO 0.01%, PbO 0.04%, HfO2 0.03%, SO3 0.02%, Mn3O4 0.01%, ignition loss 0.5%; the particle size of the dry particles is 250-320 mesh. The inkjet functional ink layer includes matte ink 131-8 (grayscale 30%-60%) and glossy ink CZN00045 (grayscale 50%-100%).
[0055] The method for preparing the ceramic tile comprises the following steps:
[0056] (1) Prepare a ceramic body layer; after powdering, spreading and drying, a ceramic body layer is obtained, and the water absorption rate is ≤0.5%; wherein the ceramic body powder is composed of the following components by mass percentage: 67.5% silicon dioxide, 18.8% aluminum oxide, 2.5% potassium oxide, 2.5% sodium oxide, 0.5% calcium oxide, 1.5% magnesium oxide, and the rest is reduced and trace impurities. The powder fineness is controlled to 1.0% on a 250 mesh sieve, and then spray granulated, and the gradation is controlled to be: less than 5% at 30 mesh, 30% at 40 mesh, 62% at 60 mesh, and no more than 5% at 100 mesh;
[0057] (2) Applying a base glaze on the surface of the ceramic body layer to form a base glaze layer; wherein the base glaze has a specific gravity of 1.84 g / mL, a flow rate of 40 s, and a glaze application amount of 450 g / m 2 ;
[0058] The base glaze is composed of the following components by mass percentage: potassium feldspar 20%, sodium feldspar 25%, air knife clay 10%, nepheline feldspar 10%, quartz 7%, wollastonite 5%, zinc oxide 3%, aluminum oxide 8%, zirconium silicate 12%;
[0059] (3) printing an inkjet printing layer on the surface of the base glaze layer;
[0060] (4) printing a functional ink layer on the inkjet printing layer (wherein: the grayscale of matte ink 131-8 is 30%-60%, and the grayscale of glossy ink CZN00045 is 50%-100%); the matte ink and the glossy ink are jetted according to a gradient grayscale, so that the matte ink and the glossy ink on the surface of the inkjet printing layer are distributed in a gradient grayscale;
[0061] Matt ink includes by mass: 4 parts of high-temperature frit, 9 parts of fused quartz, 2 parts of calcined zinc oxide, 15 parts of zirconium silicate, 5 parts of diaspore, 4 parts of pyrolysis, 6 parts of Foshan Koning polyurethane dispersant UV-531, and 55 parts of methyl oleate; the high-temperature frit includes by mass percentage: SiO249%, Al2O3 28%, K2O 6%, Na2O 5.5%, ZnO 5.5%, and CaO6%;
[0062] The glossy ink includes by mass: 4 parts of medium-temperature frit, 9 parts of fused quartz, 2 parts of calcined zinc oxide, 15 parts of zirconium silicate, 5 parts of diaspore, 3 parts of bismuth oxide, 4 parts of Foshan Koning polyurethane dispersant UV-531, and 58 parts of methyl oleate; the medium-temperature frit includes by mass percentage: SiO2 58%, Al2O3 20%, K2O 4.5%, Na2O 5.5%, ZnO
[0063] 6.5%, CaO 5.5%;
[0064] (5) applying dry particle glaze on the surface of the functional ink layer to form a surface glaze layer; wherein the dry particle glaze is composed of the following components by mass percentage: 20% dry particles, 75% suspending agent, and 5% protective glaze slurry;
[0065] The protective glaze slurry is composed of the following chemical components by mass percentage: SiO2 49%, Al2O3 16.57%, CaO5.26%, Na2O 1.68%, K2O 4.03%, Fe2O3 0.19%, ZnO 4.25%, P2O5 0.23%, BaO 5.02%, SrO
[0066] 2.36%, MgO 3.89%, TiO2 0.09%, ZrO2 0.05%, SO3 0.04%, V2O5 0.04%, ignition loss 7.30%;
[0067] The suspending agent is HB-818A, which includes the following components by mass: 32 parts of deionized water, 20 parts of methyl glycol, 20 parts of sodium carboxymethyl cellulose, 20 parts of polymethylsiloxane, 5 parts of sodium dodecylbenzene sulfonate (dispersant), and 3 parts of sodium hydroxide (pH regulator).
[0068] The specific gravity of dry granular glaze is 1.4g / mL, the flow rate is 35s, the 325 mesh residue is 1.2%, and the glaze amount is 300g / m 2 ;
[0069] (6) firing to obtain a primary finished tile product; wherein the firing temperature is 1200° C. and the firing time is 50 min;
[0070] (7) Use a 2000-mesh resin abrasive disc for micro-brush polishing for 30 seconds, wherein the pressure of the resin abrasive disc on the ceramic tile pre-finished product is 1.0 MPa, then use 8 groups of 240-mesh fiber modules for fine polishing for 50 seconds and 5 groups of 240-mesh plastic silicon carbide grinding brushes for fine polishing for 30 seconds, wherein the pressure of the fiber module and the plastic silicon carbide grinding brush on the ceramic tile pre-finished product is 1.5 MPa, and after applying anti-fouling wax water, the ceramic tile finished product is obtained.
[0071] Example 3
[0072] A ceramic tile with a bright sub-combination effect on the surface, comprising a body layer, a base glaze layer, an inkjet printing layer, an inkjet functional ink layer, and a surface glaze layer which are sequentially stacked; the surface glaze layer comprises a dry granular glaze, the dry granular glaze comprises dry particles, and the dry particles comprise, by mass percentage, SiO2 42.79%, Al2O3 17%, CaO 2.04%, Na2O 4.7%, K2O 2.96%, ZrO2 0.12%, Fe2O3
[0073] 0.09%, ZnO 6.11%, P2O5 0.14%, BaO 16.74%, SrO 5.76%, MgO 0.9%, TiO2 0.04%, CuO 0.01%, PbO 0.04%, HfO2 0.03%, SO3 0.02%, Mn3O4 0.01%, ignition loss 0.5%; the particle size of the dry particles is 250-320 mesh. The inkjet functional ink layer includes matte ink 131-8 (grayscale 30%-60%) and glossy ink CZN00045 (grayscale 50%-100%).
[0074] The method for preparing the ceramic tile comprises the following steps:
[0075] (1) Prepare a ceramic body layer; after powdering, spreading and drying, a ceramic body layer is obtained, and the water absorption rate is ≤0.5%; wherein the ceramic body powder is composed of the following components by mass percentage: 67.5% silicon dioxide, 18.8% aluminum oxide, 2.5% potassium oxide, 2.5% sodium oxide, 0.5% calcium oxide, 1.5% magnesium oxide, and the rest is reduced and trace impurities. The powder fineness is controlled to 1.0% on a 250 mesh sieve, and then spray granulated, and the gradation is controlled to be: less than 5% at 30 mesh, 30% at 40 mesh, 62% at 60 mesh, and no more than 5% at 100 mesh;
[0076] (2) Applying a base glaze on the surface of the ceramic body layer to form a base glaze layer; wherein the base glaze has a specific gravity of 1.84 g / mL, a flow rate of 40 s, and a glaze amount of 450 g / m 2 ;
[0077] The base glaze is composed of the following components by mass percentage: potassium feldspar 20%, sodium feldspar 25%, air knife clay 10%, nepheline feldspar 10%, quartz 7%, wollastonite 5%, zinc oxide 3%, aluminum oxide 8%, zirconium silicate 12%;
[0078] (3) printing an inkjet printing layer on the surface of the base glaze layer;
[0079] (4) printing a functional ink layer on the inkjet printing layer (wherein: the grayscale of matte ink 131-8 is 30%-60%, and the grayscale of glossy ink CZN00045 is 50%-100%); the matte ink and the glossy ink are jetted according to a gradient grayscale, so that the matte ink and the glossy ink on the surface of the inkjet printing layer are distributed in a gradient grayscale;
[0080] Matt ink includes by mass: 6 parts of high-temperature frit, 11 parts of fused quartz, 3 parts of calcined zinc oxide, 15 parts of zirconium silicate, 5 parts of diaspore, 3 parts of pyrolysis, 4 parts of Foshan Koning polyurethane dispersant UV-531, and 53 parts of methyl oleate; the high-temperature frit includes by mass percentage: SiO2 49%, Al2O3 33%, K2O 4.5%, Na2O 4%, ZnO4.5%, CaO5%;
[0081] The glossy ink includes, by mass, 5 parts of medium-temperature frit, 10 parts of fused quartz, 2 parts of calcined zinc oxide, 13 parts of zirconium silicate, 4 parts of diaspore, 2 parts of pyrolysis, 6 parts of Foshan Koning polyurethane dispersant UV-531, and 58 parts of methyl oleate; the medium-temperature frit includes, by mass percentage, 59% of SiO2, 17% of Al2O3, 5.5% of K2O, 6.5% of Na2O, 6.5% of ZnO, and 5.5% of CaO;
[0082] (5) applying dry particle glaze on the surface of the functional ink layer to form a surface glaze layer; wherein the dry particle glaze is composed of the following components by mass percentage: 20% dry particles, 75% suspending agent, and 5% protective glaze slurry;
[0083] The protective glaze slurry is composed of the following chemical components by mass percentage: SiO2 49%, Al2O3 16.57%, CaO5.26%, Na2O 1.68%, K2O 4.03%, Fe2O3 0.19%, ZnO 4.25%, P2O5 0.23%, BaO 5.02%, SrO2.36%, MgO 3.89%, TiO2 0.09%, HfO2 0.05%, SO3 0.04%, V2O5 0.04%, ignition loss 7.30%;
[0084] The suspending agent is HB-818A, which includes the following components by mass: 32 parts of deionized water, 20 parts of methyl glycol, 20 parts of sodium carboxymethyl cellulose, 20 parts of polymethylsiloxane, 5 parts of sodium dodecylbenzene sulfonate (dispersant), and 3 parts of sodium hydroxide (pH regulator).
[0085] The specific gravity of dry granular glaze is 1.4g / mL, the flow rate is 35s, the 325 mesh residue is 1.2%, and the glaze amount is 300g / m 2 ;
[0086] (6) firing to obtain a primary finished tile product; wherein the firing temperature is 1200° C. and the firing time is 50 min;
[0087] (7) Use a 2000-mesh resin abrasive disc for micro-brush polishing for 30 seconds, wherein the pressure of the resin abrasive disc on the ceramic tile pre-finished product is 1.0 MPa, then use 8 groups of 240-mesh fiber modules for fine polishing for 50 seconds and 5 groups of 240-mesh plastic silicon carbide grinding brushes for fine polishing for 30 seconds, wherein the pressure of the fiber module and the plastic silicon carbide grinding brush on the ceramic tile pre-finished product is 1.5 MPa, and after applying anti-fouling wax water, the ceramic tile finished product is obtained.
[0088] Figure 2 The effect diagram of the tile made in this embodiment is shown, while the tile made without printing functional ink (other things are the same as this embodiment) is as shown Figure 1 shown by Figure 2 It can be seen that the produced tiles have super flatness, bright and matte combination effect and multi-dimensional three-dimensional gloss effect, which is very high-end.
[0089] Comparative Example 1
[0090] A ceramic tile with a bright matte combination effect on the surface, which is different from Example 1 in that: the functional ink includes matte ink 131-8 (gray content 30%-60%) and bright ink CZN00045 (gray content 1%-49%); the rest is the same as Example 1.
[0091] Comparative Example 2
[0092] A ceramic tile with a bright matte combination effect on the surface, which is different from Example 1 in that: the functional ink includes matte ink 131-8 (gray content 61%-100%) and bright ink CZN00045 (gray content 50%-100%); the rest is the same as Example 1.
[0093] Comparative Example 3
[0094] A ceramic tile, which is different from Example 1 in that the content of Al2O3 in the dry particles is 24%, and the content of SrO is 0.26%; the rest is the same as Example 1.
[0095] Comparative Example 4
[0096] A ceramic tile, which is different from Example 1 in that the content of Al2O3 in the dry particles is 13%, the content of Na2O is 8.2%, and the content of K2O is 4.36%; the rest is the same as Example 1.
[0097] Comparative Example 5
[0098] A ceramic tile, which is different from Example 1 in that the content of BaO in the dry particles is 13.74%, and the content of SiO2 is 40.89%; the rest is the same as Example 1.
[0099] Comparative Example 6
[0100] A ceramic tile, which is different from Example 1 in that the content of SrO in the dry particles is 0.63%, and the content of SiO2 is 48.02%; the rest is the same as Example 1.
[0101] Comparative Example 7
[0102] A ceramic tile, which is different from Example 1 in that no protective glaze slurry is added to the dry granular glaze; the rest is the same as Example 1.
[0103] Comparative Example 8
[0104] A ceramic tile, which is different from Example 1 in that the particle size of the dry particles is 30-120 meshes; the rest is the same as Example 1.
[0105] Comparative Example 9
[0106] A ceramic tile, which is different from Example 1 in that the content of BaO in the dry particles is 17.74%, and the content of SiO2 is 44.89%; the rest is the same as Example 1.
[0107] Comparative Example 10
[0108] A ceramic tile, which is different from Example 1 in that the content of BaO in the dry particles is 0.2%, and the content of TiO2 is 0.2%; the rest is the same as Example 1.
[0109] The ceramic tiles prepared in Examples 1-3 and Comparative Examples 1-10 were tested, wherein the surface stain resistance was tested using the method in GB / T 3810.14; the friction coefficient was tested using the GB / 4100 method; the surface flatness was tested using the 1000 flatness test ruler of Keneng Ceramic Testing Equipment Co., Ltd.; and the average gloss was measured using GB / T 13891-2006 (gloss meter). The results are shown in Table 1.
[0110] Table 1
[0111]
[0112]
[0113] From Table 1, we can see that:
[0114] Examples 1-3 have good effects: stain resistance, Mohs hardness, and flexural strength all meet the standards, and the glaze surface is smooth and delicate, with a bright and sub-bright combination effect. Compared with the examples, the grayscale of the glossy ink in Comparative Example 1 is lower, and the glaze surface is smooth and delicate, but the bright and sub-bright combination effect feels weak. Compared with the examples, the grayscale of the matte ink in Comparative Example 2 is higher, resulting in slight stain absorption in the matte ink area (due to the high temperature of the matte ink 131-8, a certain peak ink volume will be used, which will cause ink penetration and stain absorption), and the glaze surface is smooth and delicate, with a bright and sub-bright combination effect.
[0115] Compared with Example 1, Comparative Example 3 is in a high temperature melting state during firing due to the high Al2O3 content (greater than 20%). After firing, the surface is prickly, and dirt is seriously absorbed and hidden. At the same time, the coloring ability is weak, the glossiness is low, the glaze surface is prickly and uneven, and there is no bright sub-combination effect. Compared with Example 1, Comparative Example 4 is in a low temperature melting state during firing due to the low Al2O3 content (less than 17%). After firing, the surface has no effect, is not wear-resistant, has no anti-slip effect, and the glaze surface is not smooth, delicate, and uneven, and there is no bright sub-combination effect.
[0116] Compared with Example 1, in Comparative Example 5, due to the low BaO content (less than 14%), the surface hardness, wear resistance and glaze brightness and color are poor, the surface is uneven and has no bright sub-combination effect. Compared with Example 1, in Comparative Example 10, due to the BaO content being adjusted to the common 0.2%, and TiO2 being selected as the core control component of the dry particles instead of BaO and set to 0.2%, the surface stain resistance is poor and the glaze brightness and color are poor, the surface is uneven and has no bright sub-combination effect. Compared with Example 1, in Comparative Example 9, due to the high BaO content (greater than 17%), the surface hardness, wear resistance and glaze brightness and color are poor, the surface is uneven and has no bright sub-combination effect.
[0117] Compared with Example 1, due to the low SrO content (less than 4.5%), the glaze surface of Comparative Example 6 is slightly cracked and the glaze color is poor, the glaze surface is uneven, and there is no bright sub-combination effect.
[0118] Compared with Example 1, Comparative Example 7 has a narrow firing temperature due to the lack of protective glaze slurry, and high and low temperatures are difficult to control, resulting in unstable quality of the ceramic tiles. The surface flatness of the ceramic tiles is unstable and has a narrow fluctuation range, and the bright sub-bonding effect has a narrow and unstable range.
[0119] Comparative Example 8 compared with Example 1: Dry particles with a smaller particle size are used. Although the surface has a certain anti-slip effect, the coarse particle size leads to serious stains, and the hand feels rough and prickly. Although there is a concave-convex feel, the glaze surface is uneven and there is no delicate and high-end feeling and bright and sub-bright combination effect.
[0120] The above is only a preferred embodiment of the present invention. The present invention is not limited to the above implementation. As long as the technical effect of the present invention is achieved by the same means, it should belong to the protection scope of the present invention. Within the protection scope of the present invention, its technical scheme and / or implementation method can have various modifications and changes.
Claims
1. A ceramic tile with a bright sub-bonding effect on the surface, characterized in that: The ceramic tile comprises a body layer, a base glaze layer, an inkjet functional ink layer, and a surface glaze layer which are stacked in sequence; the surface glaze layer comprises a dry particle glaze, the dry particle glaze comprises dry particles, and the dry particles comprise, by mass percentage, Al2O3 17%-20%, SrO 4.5%-6.5%, and BaO 14%-17%; the particle size of the dry particles is 250-400 meshes; the inkjet functional ink layer comprises matte ink and glossy ink, the gray amount of the matte ink is 30%-60%, and the gray amount of the glossy ink is 50%-100%.
2. The ceramic tile according to claim 1, characterized in that: The dry particles include, by mass percentage, SiO2 40%-45%, Al2O3 17%-20%, CaO 1.5%-3.5%, Na2O 4.5%-6.5%, K2O 1.5%-3.5%, ZrO2 0.1%-0.5%, Fe2O3 0.05%-0.15%, ZnO 5.5%-7.5%, P2O5 0.1%-0.2%, BaO 14%-17%, SrO 4.5%-6.5%, MgO 0.5%-2.0%, TiO2 0.01%-0.1%, CuO 0.01%-0.1%, HfO20.01%-0.03%, PbO0.01%-0.08%, Mn3O4 0.01%-0.05%, SO3 0.01%-0.05%, ignition reduction 0.1%-1.5%.
3. The tile according to claim 1, characterized in that: The dry particle glaze comprises, by mass percentage, 15%-25% of the dry particles, 70%-80% of the suspending agent, and 5%-15% of the protective glaze slurry.
4. The tile according to claim 3, characterized in that: The protective glaze slurry comprises, by mass percentage, SiO2 45%-50%, Al2O3 14%-17%, CaO 4.0%-6.0%, Na2O 1.0%-3.0%, K2O 3.5%-5.5%, Fe2O3 0.15%-0.25%, ZnO 3.5%-5.5%, P2O5 0.1%-0.3%, BaO 4.5%-6.5%, SrO1.5%-3.0%, MgO 3.0%-5.0%, TiO2 0.05%-0.15%, HfO2 0.0%-0.05%, SO3 0.01%-0.05%, V2O50.02-0.08%, ignition reduction 5.5%-8.5%.
5. The ceramic tile according to claim 1, characterized in that: The matte ink comprises, by mass, 4-6 parts of high-temperature frit, 9-11 parts of fused quartz, 2-3 parts of calcined zinc oxide, 13-16 parts of zirconium silicate, 3-7 parts of diaspore, 2-4 parts of bismuth oxide, 4-6 parts of polyurethane dispersant, and 45-60 parts of methyl oleate; the high-temperature frit comprises, by mass percentage, 45%-55% of SiO2, 28%-35% of Al2O3, 3.5%-6.5% of K2O, 3.5%-6.5% of Na2O, 3.5%-6.5% of ZnO, and 3.5%-5.5% of CaO 4%-6%; and / or, The bright ink comprises, by mass, 4-6 parts of medium-temperature frit, 9-11 parts of fused quartz, 2-3 parts of calcined zinc oxide, 13-16 parts of zirconium silicate, 3-7 parts of diaspore, 2-4 parts of bismuth oxide, 4-6 parts of polyurethane dispersant, and 45-60 parts of methyl oleate; the medium-temperature frit comprises, by mass percentage, 49%-59% of SiO2, 16%-22% of Al2O3, 3.5%-7.5% of K2O, 3.5%-7% of Na2O, 4.5%-7.5% of ZnO, and 4%-7% of CaO.
6. The ceramic tile according to any one of claims 1 to 5, characterized in that: An inkjet printing layer is also provided between the base glaze layer and the inkjet functional ink layer.
7. A method for preparing a ceramic tile according to any one of claims 1 to 6, comprising the following steps: preparing the green body layer; Applying ground glaze on the surface of the green body layer to form the ground glaze layer; Then, inkjet the matte ink and the glossy ink to form the inkjet functional ink layer; Applying the dry particle glaze on the surface of the inkjet functional ink layer to form the surface glaze layer; The ceramic tile is obtained by firing.
8. The preparation method according to claim 7, characterized in that: The fired product is subjected to a brushing and polishing treatment to obtain the ceramic tile; the brushing and polishing treatment The process includes: using a 2000-mesh resin abrasive disc for brush polishing for 25s-35s, a 240-mesh fiber module for fine polishing for 45s-55s, and a 240-mesh plastic silicon carbide abrasive brush for fine polishing for 25s-35s.
9. The preparation method according to claim 7, characterized in that: When forming the inkjet functional ink layer, the matte ink and the glossy ink are inkjetted so that the grayscale amounts of the matte ink and the glossy ink show a gradient change.
10. The preparation method according to claim 7, characterized in that: The specific gravity of the base glaze is 1.80g / mL-1.86g / mL, and the glaze amount is 450g / m 2 -550 g / m 2 and / or, The specific gravity of the dry granular glaze is 1.35g / mL-1.5g / mL, and the glaze application amount is 300g / m 2 -400 g / m 2 and / or, The firing conditions include: a firing temperature of 1180° C.-1210° C., and a firing time of 45 min-65 min.
Citation Information
Patent Citations
Ceramic tile and preparation method thereof
CN115028476A
Fine sand dry granular glaze, ceramic tile and preparation method thereof
CN115108722A
Ceramic rock plate imitating terrazzo surface texture and preparation method thereof
CN115872782A
Wax dry granular glaze, wax ceramic tile with 3D (three-dimensional) effect and preparation method of wax ceramic tile
CN116854375A
Matt super-soft ceramic tile with digital mold effect and preparation method of matte super-soft ceramic tile
CN118026531A
Cited By
Environment-friendly 3D micro-carving ceramic tile and preparation method thereof
CN121627433A